The effectiveness of giving silkworms Tubifex sp. enriched with curcumin on the growth and survival of jelawat fish larvae Leptobarbus hoevenii - Nur Asiah; Ayuningtyas Putri, Fadila; Heltonika, Benny (Jurnal Akuakultur Indonesia, 2026)
Curcumin is a secondary metabolite that enhances fish immunity and functions as an antibacterial and antimicrobial agent. Curcumin acts as a supplement to increase the larvae's appetite. The aim of this study was to evaluate the effect of curcumin-enriched silkworms (Tubifex sp.) on the growth and survival of jelawat fish larvae. This research was carried out in June–July 2023 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Sciences, Riau University. This study applied an experimental method using a completely randomized design (CRD) with three replications. The treatment in this study was P0 (silkworms without curcumin enrichment), P1 (silkworms enriched with curcumin 0.2 mg/kg silkworms), P2 (silkworms enriched with curcumin 0.3 mg/kg silkworms), P3 (silkworms enriched with 0.4 mg/kg curcumin), and P4 (silkworms enriched with curcumin 0.5 mg/kg silkworms). The results showed that the treatment of silkworms enriched with curcumin had a significant effect on the growth and survival of jelawat fish larvae (P